Case Study of Vocational School Human Resources Development - Sumual, Hendro; Sumual, Herry; Sompotan, Grace Jenny (JR Education, 2024)
The development of human resources in an effort to improve the quality of vocational secondary education in Indonesia is very important for recognizing the competence of graduates. This research aims to analyze human resource development, especially training and development at vocational schools. Qualitative case studies are used to obtain data and information. In-depth interviews and observations were carried out at SMK Negeri 2 Manado which had not yet become a center of excellence and SMK Negeri 5 which had become a center of excellence (SMK-PK). The research results show that human resource development, especially training and development, has a positive impact on the abilities of teachers. The aim is solely to improve the quality of graduates so that they suit the needs of the industrial world. Both schools have planned and implemented training and development to improve the abilities of educators. They need development so that there is a match between graduate competencies and the needs of the business world and the industrial world. Knowledge and skills develop along with technological developments and job demands. The training and development carried out by these two vocational education institutions is mostly a program offered by the government because it is related to funding.